Investigation of heat treatment strategies for improvement of production capacity of coin stamping dies - Sutisna, Nanang Ali; Permana, Fahyudha (Universitas Muhammadiyah Surakarta, 2021)
This paper presents a study on the production capacity of stamping dies for minting coins under different heat treatment processes, particularly austenite temperatures, using a vacuum furnace. In the study, the specimen material was made from Bohler K340 steel. The first heat treatment strategy included heating the specimens to a stable austenite temperature at 1080°C, then holding for 120 minutes and cooling rapidly with gas quenching media with a pressure of 5 bar. Tempered treatment was performed at 500°C. Another strategy was similar to the first one, except the heating temperature at 1060°C and double tempering at 575°C. After the heat treatment process, microstructure observation and hardness testing were carried out. Finally, the production of the die capacity testing on the coining machine was conducted. The results of the specimen surface photographs of the two heat treatment strategies show a significant difference in the microstructure, similarly with the hardness value obtained from single tempering is 61.98 HRC and from double tempering is 57.94 HRC. The production capacity test result indicates that the average capacity of first and second dies are 101,250 coins and 171,150 coins, respectively. It means that the second dies exceed the minimum standard production capacity of dies as determined by the Quality Control department, which is 150,000 coins.